2020
DOI: 10.3389/fpls.2020.00693
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Superresolution Visualization of Composite Plant Microtubule Organization and Dynamics

Abstract: Microtubule bundling is an essential mechanism underlying the biased organization of interphase and mitotic microtubular systems of eukaryotes in ordered arrays. Microtubule bundle formation can be exemplified in plants, where the formation of parallel microtubule systems in the cell cortex or the spindle midzone is largely owing to the microtubule crosslinking activity of a family of microtubule associated proteins, designated as MAP65s. Among the nine members of this family in Arabidopsis thaliana, MAP65-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 123 publications
(190 reference statements)
0
13
0
Order By: Relevance
“…Being produced mainly in the roots (Foo et al, 2013), strigolactones adjust both shoot (Gomez-Roldan et al, 2008;Umehara et al, 2008) and root (Ruyter-Spira et al, 2011) development in vascular plants as well as in moss caulonema (Hoffmann et al, 2014) in response to changing environmental conditions. Early grafting experiments showed that strigolactones are transported from roots to shoot in the xylem of Arabidopsis and tomato, which provided insight into strigolactone signaling regulation via their localization and transport (Kohlen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Being produced mainly in the roots (Foo et al, 2013), strigolactones adjust both shoot (Gomez-Roldan et al, 2008;Umehara et al, 2008) and root (Ruyter-Spira et al, 2011) development in vascular plants as well as in moss caulonema (Hoffmann et al, 2014) in response to changing environmental conditions. Early grafting experiments showed that strigolactones are transported from roots to shoot in the xylem of Arabidopsis and tomato, which provided insight into strigolactone signaling regulation via their localization and transport (Kohlen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The exogenous application of a synthetic strigolactone, GR24 (Umehara et al, 2008) and an inhibitor of endogenous strigolactone production, TIS108, a potent FIGURE 9 | Hypothetical model of light-dependent strigolactone effects on microtubules in Arabidopsis. (A) Regarding the overall hypocotyl phenotype, the strigolactone treatment inhibits hypocotyl growth and causes radial expansion of epidermal cells in light-grown seedlings; however, the dark-grown ones were more resistant to the changes of strigolactone content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Super-resolved 3D visualization showed disturbed organization of MTs in dividing cells of the Arabidopsis ktn1 mutant using the GFP-TUA6 MT marker ( Komis et al, 2017 ; Vyplelová et al, 2018 ). In addition, high-resolution ACLSM images of MAP65-2 labeled with eGFP or tagRFP proved its partial association with MTs visualized with TUA6-GFP or mRFP-BETA-6 TUBULIN (mRFP-TUB6) markers ( Vavrdová et al, 2020 ). ACLSM was used for dynamic localization of PM proteins with divergent functions, such as FLAGELLIN-SENSITIVE 2 (FLS2), PIN-FORMED 3 (PIN3), and BRASSINOSTEROID-INSENSITIVE 1 (BRI1), which were associated to clusters and moved at different rates ( McKenna et al, 2019 ).…”
Section: Super-resolution Microscopymentioning
confidence: 99%